Lung microbiome: new insights into bronchiectasis’ outcome - Azoicai, Alice; Lupu, Ancuta; Alexoae, Monica Mihaela; Starcea, Iuliana Magdalena; Mocanu, Adriana; Lupu, Vasile Valeriu; Mitrofan, Elena Cristina; Nedelcu, Alin Horatiu; Tepordei, Razvan Tudor; Munteanu, Dragos; Mitrofan, Costica; Salaru, Delia Lidia; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The present treatments for bronchiectasis, which is defined by pathological dilatation of the airways, are confined to symptom relief and minimizing exacerbations. The condition is becoming more common worldwide. Since the disease's pathophysiology is not entirely well understood known, developing novel treatments is critically important of utmost importance. The interplay of chronic infection, inflammation, and compromised mucociliary clearance, which results in structural alterations and the emergence of new infection, is most likely responsible for the progression the cause of the advancement of bronchiectasis. Other than treating bronchiectasis brought on caused by cystic fibrosis, there are no approved treatments. Understanding the involvement of the microbiome in this disease is crucial, the microbiome being is defined as the collective genetic material of all bacteria in an environment. In clinical practice, bacteria in the lungs have been studied using cultures; however, these days in recent years, researchers employ use next-generation sequencing methods, like such as 16S rRNA sequencing. Although the microbiome in bronchiectasis has not been thoroughly entirely investigated, what is known about it indicates suggests that Haemophilus, Pseudomonas and Streptococcus dominate the lung bacterial ecosystems communities, which exhibit they present significant intraindividual stability and interindividual heterogeneity heterogenity. Pseudomonas and Haemophilus-dominated microbiomes have been linked to more severe diseases severe disease and frequent exacerbations, but however additional research is required to fully comprehend the role function of microbiome in the evolution of bronchiectasis disease. Recent research on the lung microbiota and its connection to bronchiectasis is presented in this review. This review discusses recent findings on the lung microbiota and its association with bronchiectasis.